Transmissio actorum - Žepič, Vid (Studia Historica Slovenica, 2022)
Transmissio actorum (Aktenversendung) designates a procedural institution of the Roman-Canon criminal as well as civil procedure, which authorised lay judges in the Early Modern Era to send case files to various judicial colleges in the event of insurmountable doubts regarding the application of complex rules of the learned law. As rule, the entire case file was sent to the faculties of law, foreign municipal or regional courts as well as to the higher administrative and judicial authorities. The impartial opinions of the learned jurists may be regarded as a form of formalized expertise in the legal issues. The courts were, according to customary law, principally obliged to follow the instructions of the experts, which regularily took form of a draft judgment. The research evaluates transmissio actorum as a typical institute of reception of Roman law in the European context. Furthermore, it deals with the question whether and in what forms the institute, its predecessors or surrogates existed in the Austrian hereditary lands. The absence of the transmissio actorum should be identified as one of the causes of the delayed and less intense reception of Roman law in this part of the Holy Roman Empire.
Keywords: consilium; history of criminal law; kazensko pravo; law faculties; legal counsel; pravna mnenja; Pravna zgodovina; pravne fakultete; reception of Roman law; rimsko pravo